Pomegranate Peel as a Source of Bioactive Compounds: A Mini Review on Their Physiological Functions - Mo, Yaxian; Ma, Jiaqi; Gao, Wentao; Zhang, Lei; Li, Jiangui; Li, Jingming; Zang, Jiachen (Frontiers in Nutrition, 2022)
The production and consumption of pomegranates have always been increasing owing to their taste and nutrition. However, during fruit processing, a large number of by-products are produced, such as peels and seeds, which can lead to environmental pollution problems if not handled properly. The pomegranate peel takes up about 26%-30% of the total weight, while it contains abundant bioactive substances. This paper carries out a mini review of the characterization and physiological functions of key bioactive compounds in pomegranate peel, comprehensively assessing their effects on human health. The overview summarizes the main phenolic substances in pomegranate peel, including tannins, flavonoids and phenolic acids. Dietary fiber and other bioactive substances such as alkaloids, minerals and vitamins are also mentioned. These components act as antioxidants by improving oxidative biomarkers and scavenging or neutralizing reactive oxygen species, further contributing to their extensive functions like anti-inflammatory, anti-cancer, antibacterial and cardiovascular protection. Overall, it is envisaged that through the deeper understanding of bioactive compounds in pomegranate peel, the waste sources can be better reused for physiological applications.